Simulink models from 'Multi-temperature state-dependent equivalent circuit discharge model for lithium-sulfur batteries - Auger, Daniel; Fotouhi, Abbas; Longo, Stefano (Cranfield University, 2016)
This fileset contains a Simulink representation of the models developed in the paper 'Multi-temperature state-dependent equivalent circuit discharge model for lithium-sulfur batteries' accepted by the Journal of Power Sources on July 23, 2016. The data files can be opened with Simulink R2016a.
Keywords: lithium-sulfur battery'; 'parameter estimation'; 'system identification'; 'battery model'; 'Engineering not elsewhere classified'